Does International Migration Pay Off? The Labor Market Situation of Finnish Return Migrants Based on Longitudinal Register Data - Koikkalainen, Saara; Linnakangas, Ritva; Suikkanen, Asko (Nordic Journal of Working Life Studies, 2016)
International mobility is a form of flexible labor market adaptation available for young Nordic nationals who have the privilege of relatively easy return if life abroad does not work out. The article considers mobility as a labor market transition and examines the pre- and post-migration situation of two Finnish return migrant groups—those who lived abroad in 1999 and in 2004—based on longitudinal register data. It considers the consequences of return for an individual migrant: is it a form of failure in labor market integration in the country of destination or rather a sign of success whereby the skills, resources, and experiences gained abroad are brought back to the country of origin. Migrants who leave Finland nowadays often opt to move to other Nordic countries and are younger, more educated, and have a better socio-economic status than previous migrant generations. The article demonstrates that international migration does not deteriorate the returnees’ labor market status. While re-entry into the Finnish labor market may take some time and flexibility, mobility seems to pay off and have beneficial consequences: return migrants earn higher taxable incomes and have lower unemployment rates than their peers who only stayed in the national labor markets..